(untitled) (Research, Society and Development, 2023)
Care for patients with skin lesions has been one of the biggest challenge to the global health system. An integrative review was carried out that aimed to characterize the technological tools used to manage records coming from care for patients with skin lesions in the hospital environment from 2013 to 2023. The databases used were: Latin American Literature and of the Caribbean in Health Sciences (LILACS), Nursing Database (BDENF), Medical Literature and Retrivial System onLine (MEDLINE/PubMed®), SCOPUS (Elsevier), Institute of Electrical and Electronics Engineers (IEEE) and Web of Science. It were identified 14 publications, the majority of which were published in 2017 (03), in electronic journals (10) and specifically focused on pressure injuries (07). Most of the research was characterized as exploratory descriptive and cohort studies. It is concluded that information and communication technologies have become essential tools in data management as they have a positive impact on care management, professionals’ accessibility to patient health records and the resolution of care problems.